Post-endoscopic retrograde cholangiopancreatography pancreatitis prevention using topical epinephrine: systematic review and meta-analysis - Iqbal, Umair; Siddique, Osama; Khara, Harshit S.; Khan, Muhammad Ali; Haq, Khwaja Fahad; Siddiqui, Mohammad Arsalan; Solanki, Shantanu; Zuchelli, Tobias E.; Shellenberger, Matthew Joshua; Birk, John W. (Endoscopy International Open, 2020)
Background and study aims Post-endoscopic retrograde cholangiopancreatography pancreatitis (PEP) is a common complication of endoscopic retrograde cholangiopancreatography (ERCP). Multiple drugs and techniques have been studied for the prevention of PEP. Topical epinephrine has shown mixed results and is still not widely accepted as an alternative for prevention of PEP. We performed a systematic review and meta-analysis to evaluate the efficacy of topical epinephrine in preventing PEP.Methods A comprehensive literature review was conducted by searching Cochrane library database, Embase and PubMed up to August 2019, to identify all studies that evaluated use of topical epinephrine alone or in conjunction with other agents for prevention of PEP. Outcomes included prevention of PEP with use of topical epinephrine and evaluation of whether addiing epinephrine provides any additional benefit in preventing PEP. All analysis was conducted using Revman 5.3.Results Eight studies, including six randomized controlled trials and two observational studies with 4123 patients, were included in the meta-analysis. Overall, there was no difference in incidence of PEP in patients who underwent ERCP and were treated with epinephrine spray versus those who were not, RR = 0.63 (CI 0.32–1.24) with heterogeneity (I2 = 72 %). However, on a subgroup analysis, topical epinephrine significantly decreases the risk of PEP when compared to placebo alone (means no intervention was done including no rectal indomethacin)., RR = 0.32 (0.18–0.57). In another subgroup analysis, there was no statistically significant difference in using topical epinephrine along with rectal indomethacin in preventing PEP compared to rectal indomethacin alone RR = 0.87 (0.46–1.64).Conclusion Topical epinephrine does not provide any additional benefit in preventing PEP when used in conjunction with rectal indomethacin. In subgroup analysis, topical epinephrine appeared to decrease risk of PEP in the absence of rectal indomethacin, and could be considered when rectal indomethacin is unavailable or if there is a contraindication to its use.